Synthesis, Characterization of Chlropheniramine maleate– Molecularly Imprinted Polymers and Their Application as Sensors for the Determination of the Drug in Some Pharmaceutical Preparations - Raad, Marwa; Alsamarrai, Khalaf Farris; Al-Bayati, Yehya Kamal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New chlropheniramine maleate (CPM) selective electrochemical membranes were prepared by using chlropheniramine maleate -molecularly imprinted polymers. MIP was prepared by bulk polymerization using 2-hydroxyethyl methacrylate (2-HEMA) as monomer, ethylene glycol dimethacrylate (EGDMA) as a cross-linker and a benzoyl peroxide (BPO) as an initiator at 600C. Three CPM-MIP electrodes were constructed by using tri-tolyl Phosphate (ToCP), tris (2- ethyl hexyl) Phosphate (TEHP) and tributyl Phosphate (TBP) as plasticizers in PVC matrix.Electrode parameters including slopes, working concentrations ph. The interference effect in the presence of (Na+, Mg+2, Al+3, Glycine, Alanine, Arginine and Phenylalanine) was studied using the separated and mixed methods to determine the selectivity coefficient determination. NIP prepared by using the same composition of MIP molecularly imprinted polymer electrodes except the template (CPM). The slopes of CMPMIP are 21.00, 21.50 and 19.08 mV/ decade, linearity range for the electrodes around. (10-5 10-1) M, the stable at a pH range from 4.0 to 8.5 and lifetime ranged from 30 to 10 days. The suggested electrodes were successfully applied for the determine of CPM in some pharmaceutical preparations, which were given acceptable accuracy.